2014
DOI: 10.5935/1809-2667.20140003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de características morfológicas e agronômicas de linhagens de feijão-de-vagem em Bom Jesus do Itabapoana-RJ, com potencial de recomendação

Abstract: O objetivo deste trabalho foi realizar caracterização morfológica e agronômica da vagem das gerações F9 do programa de melhoramento do feijão de vagem, da UENF, em campo, na localidade de Bom Jesus do Itabapoana, RJ, 2010, visando ao lançamento de material melhorado para os produtores do Norte e Noroeste Fluminense. A avaliação dos caracteres da vagem foi feita segundo Formulário de Descritores Morfológicos Mínimos de Feijão (Phaseolus vulgaris L.), recomendado pelo Serviço Nacional de Proteção de Cultivares. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As for the growth habit, the snap bean can be classified as undetermined, or climbing and determined, or bush. Cultivars of indeterminate growth have a vegetative apical meristem that allows the continuous growth of plants, with they commonly achieveing higher yields when compared to bush cultivars (Wahome et al, 2013), up to more than 30 t ha -1 , as reported by Almeida et al (2014). However, such cultivars need more intense care regarding their crop management, causing a greater demands on labor, since they need tutoring, and, due to their longer cycle, they are more subject to the incidence of pests and diseases, thus increasing the overall production costs (Wahome et al, 2013;Gomes et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…As for the growth habit, the snap bean can be classified as undetermined, or climbing and determined, or bush. Cultivars of indeterminate growth have a vegetative apical meristem that allows the continuous growth of plants, with they commonly achieveing higher yields when compared to bush cultivars (Wahome et al, 2013), up to more than 30 t ha -1 , as reported by Almeida et al (2014). However, such cultivars need more intense care regarding their crop management, causing a greater demands on labor, since they need tutoring, and, due to their longer cycle, they are more subject to the incidence of pests and diseases, thus increasing the overall production costs (Wahome et al, 2013;Gomes et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The snap bean (Phaseolus vulgaris L.) is a vegetable crop that belongs to the same botanical species of common bean, in which the main difference is in the consumption of fresh pods (FILGUEIRA, 2012). In Brazil, the main cultivars have indeterminate growth habit and presents fresh pod yields of 25 to 30 t ha -1 , while determinate growth habit cultivars reach the half of this performance (ALMEIDA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%